Lei Maria da Penha e garantia de direitos humanos: Uma análise a partir de João Pessoa – Paraíba - Gregori, Juciane de (2016)
The present study, anchored in a feminist approach and contributions of queer studies, characterized as an exploratory research, predominantly of qualitative and descriptive nature, aims to analyze which advances and obstacles of the Maria da Penha Law (11.340/2006) guarantee the human rights, based in the city of João Pessoa - Paraíba. To develop this research, it‟s been performed the application of a questionnaire to feminists from different groups in the city of João Pessoa, who were invited because they were involved in a research that evaluated the resoluteness of care services to women in situations of violence in the city of João Pessoa and in other four municipalities of the state of Paraíba, which resulted in the construction of a book titled "Women in Situations of Violence: feminist perspectives on the Service Network" (FERREIRA, BARBOSA and OLIVEIRA, 2015). Based on this results, it was analyzed the advances and barriers of the current legislation, taking into consideration the territory mentioned above. It is safe to say that the Maria da Penha Law brings in its core the following message "violence against women is no longer socially acceptable" (OLIVEIRA and TAVARES, 2015, p. 23). Based on the pessoense context , it may be elucidated that this law has brought many advances towards ensuring human rights, going against the hand of ideologies revealed by patriarchal society and the principles perpetrated by a bourgeois, hegemon, racist and sexist State. Built with the feminist foundation, the law brings the point of view of domestic violence with the inclusion of transgender women and regardless their sexual orientation, seeking not only the punishment of the offender but also the victim's protection, prevention and the restraint of violence. In addition to providing increased visibility of the problem of domestic violence, the law creates specialized services to attend the victims‟ needs. On the other hand, in addition to finding difficulties to implement such actions, the greatest obstacles of the Maria da Penha Law to guarantee human rights are in the patriarchal and sexist culture, in the capitalist system and in the State structure. You can check that this legislation is presented as an advance and must be maintained and strengthened, since it is a milestone for women's rights. Due to complex and multidimensional configurations of the phenomenon in question , it is considered that the development of the emerging changes in the human rights field will only happen through a complete transformation of the material and cultural foundations that sustain society, having the need the consolidation of human right system in culture and education, throughout multiple spaces and a change in the economic and political system.